(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In Latvia the transportation of energy chips loads is carried out almost entirely by trucks. Due to the lack of hard empirical data on the compaction of energy chips loads transported by road, the currently used methodologies for the assessment of the volume of energy chips loads produce only rough estimates. In order to address this problem and fill the gap, this research paper offers: - the methodology for the determination of the coefficients for the compaction of energy chips loads depending on their transportation distance by trucks; - the values of the coefficients for the compaction of energy chips loads for different transportation distances and different kinds of trucks; - the identification and analysis of the factors that influenced the values of energy chips loads compaction coefficients.